Advances in Multimedia, Software Engineering and Computing Vol.2 c - Jin, David; Lin, Sally; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
MSEC2011 is an integrated conference concentrating its focus upon Multimedia ,Software Engineering, Computing and Education. In the proceeding, you can learn much more knowledge about Multimedia, Software Engineering, Computing and Education of researchers all around the world. The main role of the proceeding is to be used as an exchange pillar for researchers who are working in the mentioned field. In order to meet high standard of Springer, AISC series ,the organization committee has made their efforts to do the following things. Firstly, poor quality paper has been refused after reviewing course by anonymous referee experts. Secondly, periodically review meetings have been held around the reviewers about five times for exchanging reviewing suggestions. Finally, the conference organization had several preliminary sessions before the conference. Through efforts of different people and departments, the conference will be successful and fruitful.
From the content: A Quick Emergency Response Model for Micro-blog Public Opinion Crisis oriented to Mobile Internet Services: Design and Implementation -- Effectiveness Evaluation on Material Modularity Storage and Transportation by Grey-Analytical Hierarchy Process -- Study on Logistics Decision Making by Interval AHP -- A Kind of Privacy-Preserving Data Mining Algorithm Oriented to Data User -- Design of Industrial Instrument Manipulator -- Facial Expression Recognition Based on MB-LGBP Feature and Multi-Level Classification -- Semantic Processing on Big Data.
Keywords: Engineering; Software engineering; Multimedia systems; Engineering; Computational Intelligence; Multimedia Information Systems; Software Engineering/Programming and Operating Systems